Combining null-steering and adaptive filtering for acoustic feedback cancellation in a multi-microphone earpiece - Schepker, H.; Tran, Linh Thi Thuc; Nordholm, Sven; Doclo, Simon (2017)
© EURASIP 2017. Commonly adaptive filters are used to reduce the acoustic feedback in hearing aids. While theoretically allowing for perfect cancellation of the feedback signal, in practice the adaptive filter solution is typically biased due to the closedloop hearing aid system. In contrast to conventional behindthe-ear hearing aids, in this paper we consider an earpiece with multiple integrated microphones. For such an earpiece it has previously been proposed to use a fixed null-steering beamformer to reduce the acoustic feedback in the microphones. In this paper we propose to combine the fixed null-steering beamformer with an additional adaptive filter to cancel the residual feedback component in the beamformer output. We compare the combination of the fixed null-steering beamformer and different adaptive filtering algorithms including subband adaptive filtering and the prediction-error-method based fullband adaptive filtering with using either of the two approaches alone. Experimental results using measured acoustic feedback show the benefit of using the combined approach compared to using either of the two approaches to cancel the acoustic feedback.